Tissue Localization of Glycosphingolipid Accumulation in a Gaucher Disease Mouse Brain by LC-ESI-MS/MS and High-Resolution MALDI Imaging Mass Spectrometry. (December 2017) - Jones, E. Ellen; Zhang, Wujuan; Zhao, Xueheng; Quiason, Cristine; Dale, Stephanie; Shahidi-Latham, Sheerin; Grabowski, Gregory A.; Setchell, Kenneth D. R.; Drake, Richard R.; Sun, Ying
To better understand regional brain glycosphingolipid (GSL) accumulation in Gaucher disease (GD) and its relationship to neuropathology, a feasibility study using mass spectrometry and immunohistochemistry was conducted using brains derived from a GD mouse model (4L/PS/NA) homozygous for a mutant GCase (V394L [4L]) and expressing a prosaposin hypomorphic (PS-NA) transgene. Whole brains from GD and control animals were collected using one hemisphere for MALDI FTICR IMS analysis and the other for quantitation by LC-ESI-MS/MS. MALDI IMS detected several HexCers across the brains. Comparison with the brain hematoxylin and eosin (H&E) revealed differential signal distributions in the midbrain, brain stem, and CB of the GD brain versus the control. Quantitation of serial brain sections with LC-ESI-MS/MS supported the imaging results, finding the overall HexCer levels in the 4L/PS-NA brains to be four times higher than the control. LC-ESI-MS/MS also confirmed that the elevated hexosyl isomers were glucosylceramides rather than galactosylceramides. MALDI imaging also detected differential analyte distributions of lactosylceramide species and gangliosides in the 4L/PS-NA brain, which was validated by LC-ESI-MS/MS. Immunohistochemistry revealed regional inflammation, altered autophagy, and defective protein degradation correlating with regions of GSL accumulation, suggesting that specific GSLs may have distinct neuropathological effects.